Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-57718-z
|View full text |Cite
|
Sign up to set email alerts
|

Epothilone D alters normal growth, viability and microtubule dependent intracellular functions of cortical neurons in vitro

Abstract: Brain penetrant microtubule stabilising agents (MSAs) are being increasingly validated as potential therapeutic strategies for neurodegenerative diseases and traumatic injuries of the nervous system. MSAs are historically used to treat malignancies to great effect. However, this treatment strategy can also cause adverse off-target impacts, such as the generation of debilitating neuropathy and axonal loss. Understanding of the effects that individual MSAs have on neurons of the central nervous system is still i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…However, we still believe that further dosage, timing, and their synergistic effect are worth studying for these proposed multiple-molecule drug candidates. For instance, one study has demonstrated that the average transport speed of mitochondria would be affected by the different concentrations of Epothilone D [ 82 ]. The systems biology approach-based analyses in this study might provide a new perspective of finding multitarget-directed drug candidates for the therapeutics of AD.…”
Section: Resultsmentioning
confidence: 99%
“…However, we still believe that further dosage, timing, and their synergistic effect are worth studying for these proposed multiple-molecule drug candidates. For instance, one study has demonstrated that the average transport speed of mitochondria would be affected by the different concentrations of Epothilone D [ 82 ]. The systems biology approach-based analyses in this study might provide a new perspective of finding multitarget-directed drug candidates for the therapeutics of AD.…”
Section: Resultsmentioning
confidence: 99%
“…In a preclinical study, EpD increased the number of microtubules and reduced the number of axons with an abnormal morphology in young and aged Tau-transgenic mice [ 26 ]. In other mouse models of tauopathy, EpD improved cognition and reduced Tau pathology and Tau-related changes in microtubule dynamics [ 15 ]. Among the many microtubule-directed drugs, members of the Taxol family are unique because they stabilize microtubules against depolymerization [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioenergy produced by mitochondria supports assembly of microtubule-associated proteins for microtubule polymerization during cell growth and migration. Microtubule stabilizers such as Taxol and Epothilone D (EpD) play a similar role to microtubule-associated proteins and inhibit microtubule disassembly-dependent chromosome segregation, and thus can be used as anti-cancer therapies [ 15 , 16 , 17 ]. Anti-cancer agents such as microtubule stabilizers regulate mitochondrial structure, movement, and function in cancer cells, and thereby induce apoptosis [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study following treatment with this drug, MT dynamicity decreased, whilst cognition improved, as shown in the Morris Water Maze task (Barten et al, 2012). Another study in cortical neurons put in display the importance of the dose, since it can affect the mitochondrial transport (Clark et al, 2020). Studies have also shown that BM2-241027 reduces axonal dysfunction, neurotoxicity, cognitive deficits, and AD-like pathology in PS19 aged tau transgenic mice (Zhang et al, 2012).…”
Section: Microtubule Stabilizersmentioning
confidence: 98%